Zooplankton data compilation, Arctic Ocean - Part 2 - western hemisphere, 1951 - 2007 ... - Hopcroft, Russ (NSF Arctic Data Center, 2014)
This dataset is a compilation of numerous individual datasets presenting abundance and/or biomass data for zooplankton communities in the Arctic Ocean and including the Beaufort Sea, Chukchi Sea and the Canadian Archipelagos from 1951-2010. This data comes from various investigators and institutions either provided by the investigator or having been rescued from the printed literature. Every effort has been made to standardize the data in terms of currently accepted taxonomy, life stage and abundance and biomass units. HOWEVER, IT IS IMPOSSIBLE TO FULLY COMPENSATE FOR DIFFERENCES IN SAMPLING METHODS (MESH SIZE, TOW SPEED, SAMPLING DEPTH, BIOMASS CONVERSIONS), TAXONOMIC RESOLUTION AND TAXONOMIC SKILL. THIS DATA CANNOT BE USED AS IS WITHOUT UNDERSTANDING THE ASSOCIATED BIASES, WHICH CAN VARY WIDELY FROM SPECIES TO SPECIES, WITH PRONOUNCED IMPACTS ON BIODIVERSITY AND REALATIVE COMMUNITY COMPOSITION. Database Headers. Data_Base_Reference_ID- A numerical reference to the row number of the database. ...